Analisis Kemampuan Komunikasi Matematis Siswa SMP Pada Materi Himpunan - Sari, Nurlaela Windiya; Nur, Iyan Rosita Dewi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to describe the mathematical communication skills of junior high school students. This study uses a descriptive method with a qualitative approach. The research subjects were 30 students of class VII. Sampling was done by simple random sampling. The data analysis technique used is the model according to Miles & Huberman. The data collection technique uses a test of mathematical communication skills containing essays with set material. The results showed that there were 5 students in the high category with a percentage of 17%, 18 students in the medium category with a percentage of 60%, and 7 students in the low category with a percentage of 23%.